Psychological and pedagogical issues of modern education - Pankina I. A., Belokurova E. S., Matveichik T. V., Potolokova M. O., Smykovskaia T. K., Korsunova V. A., Iukhanov I. V., Chernova N. I., Eremkina N. I., Smit N. L., Ilkevich S. V., Liakhova E. G., Kugai A. I., Kugai A. I., Krutova I. A., Koreneva A. V., Deviatkova M. K., Kazakova S. V., Bezverkhaia T. N., Rodionova O. N., Gani S. V., Kvitatiani S. V., Konstantinova N. I. (Psychological and pedagogical issues of modern education, 2025)
the work analyzes the specific manifestations of «high achievements in the ballet environment and professional competence» in the context of ballet dancer’s activity, a number of recommendations have also been developed for formation of significant personal and professional competencies that minimize the negative impact of stress factors of this profession. According to the author, the formation of a holistic creative and health-saving environment will help strengthen the competitiveness of Russian ballet dancers at the global level, increase their professional self-realization and reduce the negative consequences associated with the "tragedy of the profession".
Keywords: самореализация; профессиональное выгорание; professional burnout; артист балета; ballet dancer; психоэмоциональные перегрузки; творческая здоровьесберегающая среда; psycho-emotional overload; creative health-protective environment; self-actualisation